The Time Profile of the Cost Structure in Pakistan’s Manufacturing Sector (The Pakistan Development Review, 1999)
The manufacturing sector of Pakistan has at times played the role of the leading sector of the economy. The successful experience of planned growth in the 1960s owes much to the special attention paid to the growth of manufacturing sector. Policies like the export bonus scheme, tax-holidays, subsidised import of capital, easy and subsidised loans and over-valued exchange rate, resulted in a substantial growth in the sector. However, with over-protection of the sector, nationalisation of some of the major industries in the 1970s and, later-on, over-employment in the nationalised industries, the performance of the sector started to deteriorate gradually. It is now widely believed that many of the manufacturing industries in Pakistan have become inefficient because they have not been exposed to competitive environment due to protective and distortionary policies.